O apelo comunicativo da embalagem: estudo semiótico das embalagens de água mineral - Ogasawara, Luís Alexandre Fernandes (2009)
Being sure that the formal constitution of a package is the result of several factors, like manufacturig process, features of the material used in such process, cost, ergonomy, among others, it is presupposed that the study of Packaging Design may be approached under many points of view. Thus, this research aims to study packaging design under the comunication dimension, as an element mediating the product inside the package and the consumer. Such communication takes place in peculiar space and time conditions, competing with several other stimuli during fractions of seconds of the consumer s attention in the point of sale. In such a context, for a package to be successful in its persuasive function, the package designer should link the elements in a space which would be limited, on the one hand, by the category language (to prevent the product s mischaracterization), and on the other, by the innovative features which will make it outstanding before its rival products. To fulfill the goal of this research, a historic outline of packaging and its evolution, ending both in Post-Industrial Revolution Period and its cultural consequences, will be necessary. The Consumer Society, by Jean Baudrillard, and The Society of the Spectacle, by Guy Debord and some of their unfoldments will be the basis for this research. As to the study of such a varied spectrum of communication theories which focus packaging in its communication prospect, this work intends to be guided by distinct theoretic basis, among which Shannon s, Wieners and Moles s mathematic approach of Information Theory, so as to make it possible to talk of the persuasive performance of package, linked to the concepts of redundance and innovation. Peirce s Semiotic Theory will also contribute with subsides for the the analysis of dialogues between form and content. The body of this research will be composed of mass consuming goods packages, specifically up to 510-mililiter volume mineral water, in a moment in which the segment is coming through an increasing specialization degree, making it convenient to review some patterns that, in a certain way, fill up the visual language of such packages. This fact, which is due to the need to communicate new attributes of the products, is a marketing phenomenon with communication implications and it is very rich when it is studied